Ethnopharmacological, Phytochemical, Pharmacological, and Toxicological Review on Senna auriculata (L.) Roxb.: A Special Insight to Antidiabetic Property - Nille, Guruprasad C.; Mishra, Shardendu Kumar; Chaudhary, Anand Kumar; Reddy, K. R. C. (Frontiers in Pharmacology, 2021)
Avartaki (Senna auriculata (L.) Roxb. syn. Cassia auriculata L.; Family- Fabaceae ) is a traditional medicinal plant, widely used for the treatment of various ailments in Ayurveda and Siddha system of medicine in India. Almost all the parts of the plant, such as flowers, leaves, seeds, barks, and roots have been reported for their medicinal uses. Traditionally, it has been used in the treatment of diabetes, asthma, rheumatism, dysentery, skin disease, and metabolic disorders. The principle phytochemicals in Senna auriculata (L.) Roxb. are alkaloids, anthraquinone, flavone glycosides, sugar, saponins, phenols, terpenoids, flavonoids, tannins, steroids, palmitic acid, linoleic acid, benzoic acid 2-hydroxyl methyl ester, 1-methyl butyl ester, resorcinol, α-tocopherol-β-D-mannosidase, epicatechin, ferulic acid, quercetin-3-O-rutinoside, quercetin, proanthocyanidin B1. The extracts from its different parts and their isolated compounds possess a wide range of pharmacological activities such as antidiabetic, antioxidant, anti-inflammatory, antihyperlipidemic, hepatoprotective, nephroprotective, cardioprotective, anti-atherosclerotic, anticancer, antimutagenic, antimicrobial, antiulcer, antipyretic, anthelmintic, immunomodulatory, antifertility, anti-venom, and anti-melanogenesis. The toxicological findings from preclinical studies ensured the safety of the plant, but comprehensive clinical studies are required for the safety and efficacy of the plant in humans. The current review article aimed to provide up-to-date information about Senna auriculata (L.) Roxb. covering its ethnomedicinal, phytochemical, pharmacological, and toxicological aspects with special emphasis on its clinical implications in diabetes.